Impact of Temperature and Water on Seed Germination and Seedling Growth of Maize (Zea mays L.) - Hussein Khaeim; Zoltán Kende; Márton Jolánkai; Gergő Péter Kovács; Csaba Gyuricza; Ákos Tarnawa (Agronomy, 2022)
Germination and seedling development are essential stages in a plant’s life cycle, greatly influenced by temperature and moisture conditions. The aim of this study was to determine maize (Zea mays L.) seeds’ germination and seedling development under various abiotic stresses. Eight different temperature levels, 5, 10, 15, 20, 25, 30, 35, and 40 °C, were used. Drought and waterlogging stresses were tested using 30 water levels based on one-milliliter intervals and as percentages of thousand kernel weight (TKW) at 20 and 25 °C. Seedling density and the use of antifungals were also examined. Temperature significantly affected germination duration and seedling growth, and 20 °C was found to be ideal with an optimal range of less than 30 °C. Germination occurred at 25% of the TKW. The optimal water range for seedling growth was higher and broader than the range for germination. Seed size assisted in defining germination water requirements and providing an accurate basis. The present research established an optimum water supply range of 150–325% of the TKW for maize seedling development. A total of 6 seeds per 9 cm Petri dish may be preferable over greater densities. The technique of priming seeds with an antifungal solution before planting was observed to have a better effect than applying it in the growth media.